(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2018)
South Korea is an interesting country to explore further, not only about its culture but also on its educational aspects. The development of education in South Korea well implemented due to ‘diligent’ educational reforms carried out by the government to answer the challenges of the increasingly diverse times. A long history of the history of education in South Korea has attracted the interest of authors to examine the extent of the impact of educational reform on the progress of national education. In 1999 the Government issued the Brain Korea 21st Project as one of the government’s ambitious programs to increase the competitiveness of the Korean nation. The main problem raised was “how were the application of the Brain Korea 21st Project and its impact on South Korea in 1999-2005?”. In order to elaborate on the problem, the author examined it with historical methods and research techniques using literature studies through the study of books and journals relating to research material. Based on the results of the study concluded, the First Brain Korea 21st Project’s Program implemented by the government in 1999 was a government project for seven years (1999-2005) with various objectives, and had an impact on the social and cultural aspects of gender equality which has been the issue in South Korea and the increasing number of suicides and the emergence of social inequalities between Professors at the University level. Second, the perceived impact on the economic aspect attracted back the number of foreign investors after the implementation of the Brain Korea 21st Project.